Sejarah dan Perkembangan Muhammadiyah Cabang Kecamatan Weleri Kabupaten Kendal Tahun 1930-2015 - Rinanto, Rinanto, Dr. Syamsul Hidayat, M.Ag (2016)
Muhammadiyah is of the Islamic movements in Indonesia which began in the beginning of 20 th century. At the same time there were movements in Middle East which were conducted by Ibnu Taimiyah, Muhammad bin Abdul Wahab, Jamaludin Al-Afghani, Muhammad Abduh and Muhammad Rasyid Ridho. Muhammadiyah was established in 18 November 1912 or 8 Dzulhijah 1330 by KH Ahmad Dahlan in Yogyakarta. Muhammadiyah had an impact spread all over Java Island, although it did not have its official branch offices. After Muhammadiyah got an official permission from East India government in 1912to develop it own organization soon it had official branch offices in Malang and Blora in the same year and followed by Jakarta, Surakarta, Purwokerto, Pekalongan and Pekajangan offices in 1922. The history of Muhammadiyah in Weleri city was first initiated by a teacher from Jogjakarta sent by the East India government, and by an Islamic school from Klaten. They are Raden Rahmat a representatine from Jogja and Mr Rahmadi From Klaten. It all started by a teacher from Yogakarta and a graduate from a pondok pesantren which was already known as a Kiyai, and both of them had a different style in dakwah. Yef both of them had storyideology in whichthe previous conducted the dakwah by the means of bureaucracy, while the later conducted the dakwah by visiting one mosque to others. And yef both of them same which is to keep the Islam syari'a. The Muhammadiyah Weleri branch during 1930-1960 coveraged area Weleri, Rowosari, and Ringinarum. So it can be said that Muhammadiyah in Penyangkringan village was the embrio of Muhammadiyah Weleri Branch which kiyai Rahmadi was its first chief. Muhammadiyah spreaded in Weleri by the textile trade which was brought from Klaten. Muhammadiyah developed in Weleri through education and religious study which was conducted by Muhammadiyah ulama' in this area. At that time Muhammadiyah in Weleri was not very well organized and administrated. There were data that were not recorded and not found, but Muhammadiyah conducted the spirit to keep the syari'at of Allah. Key word: Muhammadiyah, development, trade, education.